Linggarjati sebagai Sumber Belajar Sejarah bagi Generasi Muda - Mohamad Sutisna; Abdul Sukur; Nurhasan Nurhasan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Linggarjati is one of the historical sites in Indonesia that holds significant evidence of the nation’s struggle, particularly regarding diplomatic efforts to defend sovereignty after independence. This study aims to examine the potential of Linggarjati as a concrete and relevant historical learning resource for the younger generation. The research method used is descriptive qualitative, through literature study and analysis of historical values contained in the site. The results show that Linggarjati provides authentic evidence in the form of original buildings, documents, photographs, and historical objects. Utilizing this site can make history learning more meaningful, reduce the perception that history is merely memorization, and foster national awareness, love for the homeland, and critical thinking. Linggarjati serves as a bridge connecting the past with the present, offering valuable lessons for the future development of the nation.